TECHNOGENIC LOADS AND POLLUTION OF ENVIRONMENTAL ELEMENTS IN THE YASINIA TERRITORIAL COMMUNITY OF ZAKARPATTIA REGION - Oleksandr Tytarenko; Mykola Karabiniuk (Research Retrieval and Academic Letters, 2023)
The article analyzes the existing anthropogenic impacts on the natural environment and the centers of excessive impact and pollution of environmental elements in the Yasinia territorial community of Zakarpattia region. Examples of the negative impact of intensive forestry and agriculture, the critical load of recreational and tourist activities, etc. are given.